Efektivitas Model Pembelajaran Kostruktivisme terhadap Kemampuan Menyimak Siswa Kelas III Sekolah Dasar di Kota Makassar - Muliana Muliana; Supriadi Supriadi; Jusmaniar Jusmaniar (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: The Effectiveness of the Constructivism Learning Model on the Listening Ability of Grade III Elementary School Students in Makassar City. The research aims to improve the speaking skills of grade III students in Makassar City. This study used an experimental pretest approach, postest control group. Pretest-Posttest Control Group design. The population of this study was class III A as many as 15 people and class III B as many as 15 students at SDN Pulau Kodingareng Makassar City. Its data collection techniques using; listening and observation tests. Data analysis techniques use descriptive statistical analysis and inferential statistics. The results of this study show that there are differences in learning achievement between experimental classes and control classes using a learning model of constructivism of Indonesian language materials, especially in improving students' listening skills. The difference in learning achievement is due to the difference in factors according to the use of models combined with media with appropriate techniques such as the use of constructivism models. shows that there is a constructivism model for the effectiveness and improvement of students' listening skills, This is evidenced by the increase that occurs at the time of improvement that occurs during the application of the learning model.